How Words Transcend and Pictures Immerse: On the Association Between Medium and Level of Construal. (March 2015) - Rim, SoYon; Amit, Elinor; Fujita, Kentaro; Trope, Yaacov; Halbeisen, Georg; Algom, Daniel
Drawing from construal level theory, we test the hypothesis that words promote thinking of events in terms of their abstract and central features (i.e., high-level construal), whereas pictures promote thinking in terms of more concrete and idiosyncratic features (i.e., low-level construal). In Experiments 1a and 1b, we found that verbal (vs. pictorial) presentation of objects led to broader, more inclusive categorization of those objects. In Experiment 2, we found that word (vs. picture) priming led to greater global (vs. local) processing of subsequent perceptual information. Finally, in Experiments 3 and 4, we tested the opposite direction of causality. Thinking about high-level "why" versus relatively low-level "how" (Experiment 3) and thinking about high-level categories versus relatively low-level exemplars (Experiment 4) led to more verbal versus pictorial thought. These findings provide converging evidence that medium (word, picture) is associated with level of construal.